(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
A small collection of Ladinian ammonoids from Mt. Svilaja (External Dinarides) is here described for the first time. The ammonoids were collected from a thick succession, which yielded in its lower part the classic Lower Triassic ammonoid faunas of Muæ, known since the XIX century. The collection comes from an interval yielding conodonts of the hungaricus Assemblage zone, and is composed of leiostraca (Proarcestes) and trachyostraca ammonoids. The latter consists of the new genus Alkaites, and the new species A. dinaricus, Detoniceras svilajanus and Argolites trinodosus. Alkaites n. gen. is characterised by involute coiling, v-shaped ventral side and five spiral rows of nodes. D. svilajanus n. sp. is distinguished by flat ventral side, and four rows of nodes with peculiar ratio 1:1:2:2 between perimbilical,1st lateral, 2nd lateral, and ventrolateral nodes. A. trinodosus n. sp. is characterised from any other species of Argolites by three rows of nodes. At the present the new genus Alkaites and the three new species are known only from the study area. The dating of the new taxa is done by indirect correlations based on the distribution of Detoniceras and Argolites in other sections of the Southern Alps, as well as on the calibration of the hungaricus Assemblage zone with the ammonoid standard scale. The inferred age is Gredleri Zone (Lower Ladinian).